Weight stigma and psychological distress: A moderated mediation model of social identification and internalised bias. (December 2020) - Curll, Sonia L.; Brown, Patricia M.
Highlights: We tested an extended rejection-identification model among higher-weight adults. Stigma was positively linked to social identification and psychological distress. Social identification mediated the link between weight stigma and distress. This indirect effect was moderated by internalised weight bias. Social identification may benefit higher-weight adults with low internalised bias. Abstract: Links between weight stigma and negative health outcomes are well documented, but risk and protective factors remain unclear. In this study, 458 higher-weight Australian adults completed online self-report measures of perceived weight stigma, weight-based social identification (identity centrality), internalised weight bias, and psychological distress. Associations between these variables were investigated in line with the rejection-identification model and the social identity approach to health. Perceived stigma was positively associated with social identification and psychological distress. Simple mediation analysis showed a positive indirect effect of perceived stigma on psychological distress through social identification. However, moderated mediation analysis revealed that this indirect effect was dependent on internalised bias. Among participants who reported low internalised bias, social identification was associated with lower psychological distress; but for those with high internalised bias, this relationship was reversed. Findings suggest that perceived weight stigma, weight-based social identification, and internalised weight bias are key factors that should be considered together in the design and evaluation of interventions to improve the mental health of higher-weight individuals.